2005
DOI: 10.1182/blood-2004-05-2044
|View full text |Cite
|
Sign up to set email alerts
|

Only the CD62L+ subpopulation of CD4+CD25+ regulatory T cells protects from lethal acute GVHD

Abstract: IntroductionCD4 ϩ CD25 ϩ regulatory T (Treg) cells are potent modulators of immune responses. We and others have demonstrated that donorderived CD4 ϩ CD25 ϩ Treg cells could suppress lethal acute graft-versus-host disease (aGVHD) in murine models of allogeneic bone marrow transplantation. [1][2][3] In these models, cotransplantation of Treg cells with conventional donor T cells controlled the expansion of alloaggressive T cells in recipient animals, thereby interfering with one of the major events in the initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
273
3
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 372 publications
(295 citation statements)
references
References 30 publications
17
273
3
2
Order By: Relevance
“…Several studies have tried to solve this dilemma. It has been shown that CD4 + Treg from the donor or recipient can control GVHD after BM transplantation [21,[55][56][57][58]. In previous studies, we have found that donor DN-Treg could suppress donor CD8 + T cells, which caused GVHD in a single MHC-mismatched model [32].…”
Section: Discussionmentioning
confidence: 90%
“…Several studies have tried to solve this dilemma. It has been shown that CD4 + Treg from the donor or recipient can control GVHD after BM transplantation [21,[55][56][57][58]. In previous studies, we have found that donor DN-Treg could suppress donor CD8 + T cells, which caused GVHD in a single MHC-mismatched model [32].…”
Section: Discussionmentioning
confidence: 90%
“…Whereas CCR7-deficient naive-like Treg fail to recirculate through LN, resulting in an almost complete abolishment of their ability to inhibit the proliferation of naive T cells at this site, effector/memory-like Treg from CCR7 -/-mice display an increased accumulation in inflamed sites, which was accompanied by an enhanced suppression of the inflammatory reaction. CCR7 expression was predominantly observed on naive-like Treg [3,5,6,11,[31][32][33][34] and CCR7-expressing CD62L high CD25 + CD4 + Treg were found to be very efficient in preventing the development of autoimmunity [5] or in suppressing graft-versus-host disease [35,36]. It was suggested that Treg recirculation through LN mediated by CCR7 and CD62L is a prerequisite to suppress priming of autoreactive effector cells.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that differential expression of both CD62L and CD27 on CD4ϩ,CD25 high Treg might be useful in distinguishing Treg subsets by their migratory properties (43)(44)(45). It has been proposed that CD27Ϫ and CD62LϪ Treg are destined to enter the periphery, whereas lymph nodehoming Treg express CD62L and CD27.…”
Section: Discussionmentioning
confidence: 99%